(untitled) (Teacher’s World: Journal of Education and Research, 2024)
The integration process of technology in education is related to a large extent with teachers; attitude, their motivation and access, ease of use and usefulness of new innovation. Therefore, the paper aims to explore the teachers’ attitude toward ICT integration in classroom instruction. The study follows a quantitative research design following multistage stratified sampling technique whereby survey instrument has been used to collect data. The SPSS software is employed for statistical analysis of data. Results display that the teachers possess positive attitude toward ICT integration in Bangladesh and Global Studies (BGS) classrooms at secondary level. Additionally, the analysis explores the school location, school types, gender and confidence, which have potential impact and change to the teachers’ attitude toward ICT integration. The results of this study would be helpful to foster the ICT integration in school education for creating constructive teaching-learning environment. Although the study focuses on secondary school BGS teachers but it could have significant influence in all stage of education in Bangladesh. Teacher’s World: Journal of Education and Research, 49 (1), 77-94